Plesiomonas shigelloides infection induced ferroptosis and apoptosis in hepatopancreas of zig-zag eel (Mastacembelus armatus) - Zhide Yu; Xiaoli Yin; Wenshi Zhu; Yiman Chen; Li'nan Zhang; Hu Shu (Fish & Shellfish Immunology, 2025)

Effects of compound probiotics on intestinal and liver transcriptome, immunity and disease resistance of zig-zag eel (Mastacembelus armatus) - Yuwei Feng; Yiman Chen; Zhiting Zuo; Xianshan Lin; Qiaoyi Chen; Along Gao; Zhide Yu; Chong Han; Hu Shu (Aquaculture, 2025)

Effects of hypoxia and reoxygenation on energy metabolism, immune response, and apoptosis in orange-spotted grouper (Epinephelus coioides) - Yuxin Wu; Yiran Lin; Bing Lin; Yukun Huang; Zhide Yu; Yonghao Ma; Yuwei Feng; Qiaoyi Chen; Along Gao; Hu Shu (Frontiers in Marine Science, 2024)
Hypoxia is an unfavorable environmental condition that produces diverse negative effects in fish. High-density cultures of Epinephelus coioides are more likely to experience hypoxic conditions than those in natural environments. To assess the effects of hypoxia on E. coioides , we examined the related enzyme activities and gene expression after 48 h of hypoxia and 24 h of dissolved oxygen (DO) recovery. Under hypoxic stress (DO: 1.2 ± 0.1 mg/L), the energy supply mode of fish changed from aerobic metabolism to anaerobic metabolism, and the serum glucose content and lactate dehydrogenase activity were significantly upregulated. Total protein, hepatic glycogen, and two key regulatory enzymes (i.e., hexokinase and pyruvate kinase) were differentially expressed in the liver, and mRNA expression of three genes (i.e., LDHA , GLUT1 , and MCT2 ) also showed a high expression trend. In serum, three immune-related enzymes (i.e., alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase) were found to be involved in regulation by hypoxia and showed different levels of changing patterns. Expression of inflammatory genes (i.e., IL-8 , IFNγ , MyD88 , and NF-kB ) were significantly regulated in liver. With prolongation of hypoxic stress, high expression of apoptotic genes (i.e., p53 , Bax , Bcl-2 , and Caspase-9 ) was closely related to the degree of apoptosis in the liver. Our investigation of the changes in energy metabolism, immune response, and apoptosis of E. coioides under hypoxia and reoxygenation (DO, 6.0 ± 0.1 mg/L) provides a theoretical bases for healthy aquaculture and selection of varieties with tolerance to hypoxia.

Completely blocking the feminization by replacing Limnodilus spp. with Artemia salina to feeding XY Zig-zag eel (Mastacembelus armatus) - Baoyue Lu; Xiaowen Xue; Zhide Yu; Linan Zhang; Jinlin Yang; Yuwei Feng; Yiman Chen; Chong Han; Xiaoli Yin; Hu Shu (Aquaculture, 2024)

Development of genetic sex markers of zig-zag eel (Mastacembelus armatus) by a NGS method - Weijian Qin; Chong Han; Jinlin Yang; Zhide Yu; Yuwei Feng; Yuxin Wu; Baoyue Lu; Mingxiang Cui; Hu Shu (Aquaculture, 2023)